Short synthesis, X-ray and conformational analysis of a cyclic peracetylated l-sorbose-derived nitrone, a useful intermediate towards N–O-containing d-gluco-iminosugars. (18th September 2018) - Tangara, Salia; Kanazawa, Alice; Fayolle, Martine; Philouze, Christian; Poisson, Jean-François; Behr, Jean-Bernard; Py, Sandrine
Abstract : A crystalline peracetylated nitrone underwent regio- and stereoselective 1, 3-dipolar cycloaddition with alkynes, affordingd - gluco -configured isoxazolines as a new class of iminosugars. Abstract : The synthesis of the peracetylated ketonitrone4 is described in four steps froml -sorbose. This cyclic nitrone is crystalline and proved to preferentially adopt a 4 H3 conformation with all acetate groups in pseudo-axial orientation. Nitrone4 undergoes regioselective cycloadditions with alkynes, affording tetra- O -acetyl-isoxazolines with good yields and stereoselectivities (4 : 1 to 9 : 1 diastereomeric ratio). Nitrone4 and the obtained isoxazolines were smoothly deacetylated to produce the polyhydroxylated nitrone5 and novel iminosugars containing an isoxazoline motif. Evaluation of their glycosidase inhibitory activity demonstrated their rather weak, but selective affinity for a variety of enzymes.